Development and validation of a novel HILIC method for the quantification of low-levels of cuprizone in cuprizone-containing chow - Fengmei Zheng (Nature Portfolio, 2021)
Abstract Cuprizone is an amide compound that has been wildly used in various animal studies, such as in the investigation of remyelination in mouse model. It is important to control the amount of cuprizone dosed in animals to be consistent as different amounts may lead to different clinical observations. Cuprizone is usually administrated as a minor component (i.e., 0.3%) of a mixture with powdered or pelleted rodent chow. Its low content, combined with the complex nature of chow, represents a significant challenge for the quantification of cuprizone in the mixture. To the best of our knowledge, no method has been reported in the literature so far. In this study, a simple, selective, and sensitive hydrophilic interaction liquid chromatographic method was developed for the quantification of cuprizone in cuprizone pre-clinical formulations. The analytical method comprises a fast ultrasound assisted extraction with acetonitrile/water as a solvent followed by gradient separation using a Waters Xbridge HILIC column with 0.1% TFA in water and acetonitrile as mobile phases and UV detection at 220 nm. The specificity, linearity, accuracy, repeatability, and limit of quantitation (LOQ) of the method were established. The method was determined to be linear in the range of 10–200 μg/mL. Accuracy was assessed by spiking a chow placebo with various amounts of a cuprizone reference standard to achieve target concentration levels and the recoveries were within the acceptance criterion of 90–110% of the target concentrations. Repeatability was demonstrated at the nominal concentration of 100 µg/mL and LOQ level of 2.5 μg/mL. This method has been demonstrated to be suitable for its intended use and has been successfully applied to the quantification of low levels of cuprizone in chow formulations. It was found that the cuprizone content in chow could varied significantly between batches and the potential causes of the variability were investigated.